2020
DOI: 10.1002/elan.201900751
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensor Based on Reduced Graphene Oxide, Gold Nanoparticles and Molecular Imprinted Over‐oxidized Polypyrrole for Amoxicillin Determination

Abstract: An electrochemical sensor for amoxicillin (AMX) detection based on reduced graphene oxide (RGO), molecular imprinted overoxidized polypyrrole (MIOPPy) modified with gold nanoparticles (AuNPs) is described in this work. The electrochemical behavior of the imprinted and non‐imprinted polymer (NIP) was carried out by cyclic voltammetry (CV) and impedance spectroscopy (IS). The structure and morphology of the prepared MIP sensor were characterized by scanning electron microscopy (SEM), UV‐Visible, Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…The electroanalytical results related to the lowest limit of detection and the sensitivity obtained with the CuBi/CNF electrode are better than those reported by Essousi et al [ 28 ], and showed the possibility of a practical application of this electrode in the detection of amoxicillin in the aqueous solution. The practical analytical application of the CuBi/CNF paste electrode using the DPV method was established by determining AMX in a water sample.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The electroanalytical results related to the lowest limit of detection and the sensitivity obtained with the CuBi/CNF electrode are better than those reported by Essousi et al [ 28 ], and showed the possibility of a practical application of this electrode in the detection of amoxicillin in the aqueous solution. The practical analytical application of the CuBi/CNF paste electrode using the DPV method was established by determining AMX in a water sample.…”
Section: Resultsmentioning
confidence: 56%
“…The linearity between the anodic current recorded at the potential value of +0.54 V/SCE and the AMX concentration allowed us to determine the detection sensitivity, which is higher for modified CuBi/CNF (181 µA mM −1 cm −2 ) in comparison with the CNF paste electrode (133 µA mM −1 cm −2 ) (the results of linearizations are not shown here). The electrochemical response is based on the oxidation peak, which characterizes the one electron involving an oxidation reaction of the phenolic substituent to a respective carbonyl group on the side chain of the AMX molecule [ 28 ]. One corresponding cathodic peak due to the reduction process is noticed for CuBi/CNF in comparison with the CNF electrode that did not exhibit the cathodic peak in this anodic range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, metal nanoparticles [2], various metal oxides nanoparticles [3], carbonaceous nanomaterials [4], and nanocomposites [5] are used as electrode-modified material, which provides many advantages (high surface-to-volume ratio, strong catalytic properties, and effective adsorption ability) to the electrochemical sensor [1]. As an electrode modification material, gold [6], silver [7], platinum [8], copper [9], and nickel [10] nanoparticles have revealed good performances in electrochemical applications. Metal oxides such as nickel oxide, zinc oxide, and copper oxide are extensively used as electrode modifiers in sensor fabrication due to their low resistivity, good electrical properties, and remarkable redox properties [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to several specific features of graphene such as I): excellent electronic and thermal conductivity, II) high active surface area because of the micro‐sized pores, III): active sites for mass and electron transfer and IV): accessibility thermal stability [1, 2], it is one of the best candidates in sensors and biosensors fabrication, energy production, and storage application. Two dimensional (2D) graphene has advantages like high specific surface area and excellent electrical conductivity [3, 4]. It has been used in sensors, biosensors, field‐effect transistors, and transparent conductors.…”
Section: Introductionmentioning
confidence: 99%